Waterborne energy-collecting wear-resistant piezoelectric composite coating for road and preparation method thereof
By introducing strip-shaped composite electrospinning fiber membranes and inorganic particles into the coating of the road energy-gasplit device, the piezoelectric performance and wear resistance are improved, and the problems of high cost and complex installation of existing devices are solved, achieving efficient energy collection and cost reduction effects.
Patent Information
- Application Number
- CN202510076114.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing road energy-gathering devices are costly and complex in construction and packaging, making it difficult to effectively collect energy during traffic.
A road-based water-based integrated wear-resistant piezoelectric composite coating is developed. By introducing strip-shaped composite electrospinning fiber membranes and inorganic particles into the coating, the synergistic effect between materials is used to improve the piezoelectric performance and wear resistance of the coating.
The vibration mechanical energy applied to the coating surface in daily life is realized to convert the vibrational mechanical energy applied to the coating surface into electrical energy, and the mechanical properties and chemical stability of the road marking coating are improved by doping high-hardness ceramic powder, reducing the cost of the device and installation complexity.
Smart Images

Figure BDA0005247137770000101 
Figure BDA0005247137770000111 
Figure HDA0005247137780000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of road engineering materials, and specifically relates to a water-based energy-collecting wear-resistant piezoelectric composite coating for roads and a preparation method thereof. Background Art
[0002] With the continuous consumption of traditional energy, finding green and sustainable energy has become a vital issue. At present, materials and equipment for collecting green energy in daily environment have received a lot of research attention. In daily traffic, a large number of vehicles lose energy in the form of vibration and heat generated by contact with the road during driving. Therefore, energy collection during traffic driving is one of the major sources of clean energy. Most of the previous research on road energy collection has focused on preparing ceramic and composite film piezoelectric materials, which are then buried in the road as energy collection devices after complex packaging. Although this has proven to be feasible in terms of collection efficiency, since most of them are buried several centimeters deep in the road, there are high costs in terms of construction and packaging. Therefore, it is necessary to develop a new type of road energy collection device that can withstand repeated wheel rolling by vehicles and reduce installation costs. In view of the above technical status quo and the needs of the development of intelligent materials, it is urgent to develop a composite coating with energy collection properties, which can convert the vibration mechanical energy applied to the coating surface in daily life into electrical energy through the positive piezoelectric effect of piezoelectric materials, and improve the mechanical properties and chemical stability of road marking coatings by doping with high-hardness ceramic powders, so as to reduce the high cost and complex installation of road energy collection devices. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide a water-based energy-harvesting and wear-resistant piezoelectric composite coating for road use and a preparation method thereof. The preparation method introduces strip-shaped composite electrospun fiber membranes and inorganic particles into the coating, and utilizes the synergistic effect between the materials to enhance the piezoelectric properties and wear resistance of the coating.
[0004] Technical solution: A water-based energy-collecting wear-resistant piezoelectric composite coating for roads, the preparation method of which comprises the following steps: S1. Add a dispersant, a defoamer and a wetting agent to water in sequence and stir evenly, then add the strip composite electrospun fiber membrane and stir to obtain a suspension A; S2. Nano-titanium dioxide powder, heavy calcium powder, nano-inorganic lead zirconate titanate powder and low-mesh inorganic lead zirconate titanate powder were sequentially added to the suspension A obtained in S1 and stirred thoroughly to obtain a suspension B; S3. The suspension B obtained in S2 was mixed with an acrylic emulsion and stirred to obtain a slurry; S4. First, methanol is added to the slurry obtained in S3, and then a defoamer, a thickener, alcohol ester twelve and water are added in sequence, and the piezoelectric composite coating is obtained after stirring. Preferably, the mass ratio of the dispersant, the defoaming agent, the wetting agent and the strip-shaped composite electrospun fiber membrane in S1 is 1.5-5: 0.2-0.3: 0.2-0.3: 8-10. Preferably, the mass ratio of the nano titanium dioxide powder, the heavy calcium powder, the nano inorganic lead zirconate titanate powder and the low-mesh inorganic lead zirconate titanate powder in S2 is 4-10:10-20:5-10:30-50. Preferably, the mass ratio of the suspension B to the acrylic emulsion in S3 is 7-20:25-35, and the solid content of the acrylic emulsion is 55%. Preferably, the mass ratio of the defoamer, thickener, alcohol ester dodecahydrate and water in S4 is 0.2-0.3:0.05-0.1:3-5:2-8. Preferably, the method for preparing the strip-shaped composite electrospun fiber membrane in S1 comprises the following steps: S1-1. Take PVDF and PBZ in a mass ratio of 2 to 7:3 to 8, add them to a DMF / acetone solution in a volume ratio of 6:4, and stir to obtain a homogeneous solution with a mass fraction of 10 to 25 wt%; S1-2. To the homogeneous solution obtained in S1-1, hyperbranched graphene oxide and hyperbranched barium titanate in a mass ratio of 1 to 8:1 to 15 are added, and after ultrasonication, an electrospinning solution with a mass fraction of 5 to 15 wt% is obtained; S1-3. The electrospinning solution obtained in S1-2 was spun at a voltage of 15 to 20 kV, a flow rate of 0.8 to 1.5 mL / h and a receiving distance of 15 to 20 cm to obtain an electrospun fiber membrane; S1-4. The electrospun membrane obtained in S1-3 was cut to obtain an aspect ratio of 2 to 5:1 and an area of 0.1 to 0.5 cm 2 Strip-shaped composite electrospun fiber membrane. Preferably, the preparation method of the hyperbranched graphene oxide in S1-2 comprises the following steps: S2-1. The graphene oxide was dispersed in water and ultrasonically treated, followed by adding hyperbranched poly(ethylene amide) and catalytic tetrabutylammonium bromide and stirring to obtain a suspension; S2-2. The suspension obtained in S2-1 is reacted at 80-150° C. for 18-24 hours, washed and dried to obtain hyperbranched graphene oxide. Preferably, the preparation method of hyperbranched barium titanate in S1-2 comprises the following steps: S3-1. Add hyperbranched polyamide into DMAc and fully dissolve it, then add barium titanate and ultrasonically disperse it to obtain a suspension; S3-2. Heat the suspension obtained in S3-1 at 35-55°C with stirring for 20 hours, then filter and wash to obtain hyperbranched barium titanate. Preferably, the mass ratio of hyperbranched polyvinyl amide to graphene oxide in S2-1 is 10-15:1-3, and the mass fraction of the suspension is 3-10wt%. Preferably, the mass ratio of the hyperbranched polyamide to the barium titanate in the S3-1 is 15-20:1-7, and the mass fraction of the suspension is 4-8wt%. Preferably, in one embodiment, the steps of preparing a piezoelectric coating from the energy-collecting and wear-resistant piezoelectric composite coating prepared by the method are as follows: S11. The resulting coating is evenly applied to a metal plate to obtain an initial coating having a thickness of 150 to 250 μm; S12. The initial coating obtained in S11 is heated and cured at 120 to 180° C. for 20 to 40 minutes to obtain a cured coating; S13. The surface of the cured coating obtained in S12 was polished, and a conductive silver paste was applied and cured at room temperature for 24 hours; S14. Polarize the coating obtained in S13 with a voltage of 10 to 18 kV for 15 to 20 minutes to obtain a road-use water-based energy-harvesting wear-resistant piezoelectric composite coating. Beneficial effects: The piezoelectric coating of the present invention has the following advantages: 1. The present invention introduces a strip-shaped composite electrospun membrane into the coating. The strip-shaped electrospun membrane has good dispersion performance in the coating and is porous. The porous material has a higher energy density and piezoelectric energy collection figure of merit, which helps to improve the response speed and sensitivity of the material to external stimuli, thereby improving the piezoelectric performance; 2. During the electrospinning process, the dipoles in the nanofiber crystals of the PVDF in the strip composite electrospinning membrane of the present invention are oriented under the action of a strong electric field and mechanical stretching, thereby achieving in-situ polarization to obtain highly electrically active β-phase PVDF, thereby improving the piezoelectric properties; 3. The hyperbranched modified graphene and barium titanate in the present invention reduce the agglomeration between particles and can be better dispersed in the electrospinning solution. In addition, the hyperbranched modified graphene and barium titanate can be used as nucleating agents and physical cross-linking points to promote the formation of β phase in PVDF while improving the orientation of PVDF molecular chains, thereby improving piezoelectric properties; 4. In the present invention, PBZ undergoes open-loop crosslinking during the curing process, thereby increasing the degree of crosslinking and forming a dense surface, thereby improving the wear resistance of the coating. In addition, the porosity is also reduced during the open-loop crosslinking process, making the electric field distribution more uniform, thereby improving the piezoelectric response efficiency of the material. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is the electrical signal of Example 7 under the impact hammer. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 A water-based energy-collecting wear-resistant piezoelectric composite coating for roads, the preparation method of which comprises the following steps: S1. Add dispersant (sodium salt of polycarboxylate), defoamer (mineral oil) and wetting agent (BYK 346) to water in sequence and stir evenly, then add strip composite electrospun fiber membrane, wherein the mass ratio of dispersant, defoamer, wetting agent and strip composite electrospun fiber membrane is 1.5:0.2:0.2:8, and stir to obtain suspension A; S2. To the suspension A obtained in S1, nano titanium dioxide powder, heavy calcium powder, nano inorganic lead zirconate titanate powder and low-mesh inorganic lead zirconate titanate powder in a mass ratio of 4:10:5:30 are added in sequence and stirred thoroughly to obtain a suspension B; S3. The suspension B obtained in S2 was mixed with the acrylic emulsion, the mass ratio of the suspension B to the acrylic emulsion was 7:25, and a slurry was obtained after stirring; S4. methanol is first added to the slurry obtained in S3, and then a defoamer (mineral oil), a thickener (hydroxymethyl cellulose), alcohol ester twelve and water are added in sequence, wherein the mass ratio of methanol, defoamer, thickener, alcohol ester twelve and water is 0.2:0.05:3:2, and a piezoelectric composite coating is obtained after stirring; The method for preparing the strip-shaped composite electrospun fiber membrane in S1 comprises the following steps: S1-1. Take PVDF and PBZ in a mass ratio of 2:3, add them to a DMF / acetone solution in a volume ratio of 6:4, and stir to obtain a homogeneous solution with a mass fraction of 10wt%; S1-2. To the homogeneous solution obtained in S1-1, hyperbranched graphene oxide and hyperbranched barium titanate were added in a mass ratio of 1:1, and an electrospinning solution with a mass fraction of 5 wt% was obtained after ultrasound; S1-3. The electrospinning solution obtained in S1-2 was spun at a voltage of 15 kV, a flow rate of 0.8 mL / h and a receiving distance of 15 cm to obtain an electrospun fiber membrane; S1-4. The electrospun membrane obtained in S1-3 was cut to obtain a membrane with an aspect ratio of 2:1 and an area of 0.1 cm 2 Strip-shaped composite electrospun fiber membrane; Wherein, the preparation method of the hyperbranched graphene oxide in S1-2 comprises the following steps: S2-1. Graphene oxide is dispersed in water and ultrasonically treated, and then hyperbranched poly(ethylene amide) and catalytic tetrabutylammonium bromide are added, the mass ratio of hyperbranched poly(ethylene amide) to graphene oxide is 10:1, and stirred to obtain a suspension with a mass fraction of 3 wt%; S2-2. The homogeneous solution obtained in S2-1 is reacted at 80°C for 18h, and then washed and dried to obtain hyperbranched graphene oxide; The preparation method of the hyperbranched barium titanate in S1-2 comprises the following steps: S3-1. The hyperbranched polyamide was added to DMAc and fully dissolved, followed by the addition of barium titanate, the mass ratio of the hyperbranched polyamide to barium titanate being 15:1, and ultrasonic dispersion was performed to obtain a suspension having a mass fraction of 4 wt %; S3-2. The suspension obtained in S3-1 was heated at 35°C and stirred for 20 hours, and then filtered and washed to obtain hyperbranched barium titanate. Example 2 A water-based energy-collecting wear-resistant piezoelectric composite coating for roads, the preparation method of which comprises the following steps: S1. dispersant (sodium salt of polycarboxylate), defoamer (mineral oil) and wetting agent (BYK 346) were added to water in sequence and stirred evenly, and then strip composite electrospun fiber membrane was added, wherein the mass ratio of dispersant, defoamer, wetting agent and strip composite electrospun fiber membrane was 5:0.3:0.3:10, and the suspension A was obtained by stirring; S2. To the suspension A obtained in S1, nano titanium dioxide powder, heavy calcium powder, nano inorganic lead zirconate titanate powder and low-mesh inorganic lead zirconate titanate powder in a mass ratio of 10:20:10:50 were added successively and stirred to obtain a suspension B; S3. The suspension B obtained in S2 was mixed with the acrylic emulsion, the mass ratio of the suspension B and the acrylic emulsion was 20:35, and a slurry was obtained after stirring; S4. methanol is first added to the slurry obtained in S3, and then a defoamer (mineral oil), a thickener (hydroxymethyl cellulose), alcohol ester twelve and water are added in sequence, wherein the mass ratio of methanol, defoamer, thickener, alcohol ester twelve and water is 0.3:0.1:5:8, and a piezoelectric composite coating is obtained after stirring; The method for preparing the strip-shaped composite electrospun fiber membrane in S1 comprises the following steps: S1-1. Take PVDF and PBZ in a mass ratio of 7:8, add them to a DMF / acetone solution in a volume ratio of 6:4, and stir to obtain a homogeneous solution with a mass fraction of 25wt%; S1-2. To the homogeneous solution obtained in S1-1, hyperbranched graphene oxide and hyperbranched barium titanate in a mass ratio of 8:15 were added, and after ultrasound, an electrospinning solution with a mass fraction of 15 wt% was obtained; S1-3. The electrospinning solution obtained in S1-2 was spun at a voltage of 20 kV, a flow rate of 1.5 mL / h and a receiving distance of 20 cm to obtain an electrospun fiber membrane; S1-4. The electrospun membrane obtained in S1-3 was cut to obtain a membrane with an aspect ratio of 5:1 and an area of 0.5 cm 2 Strip-shaped composite electrospun fiber membrane; Wherein, the preparation method of the hyperbranched graphene oxide in S1-2 comprises the following steps: S2-1. Graphene oxide is dispersed in water and ultrasonically treated, and then hyperbranched poly(ethylene amide) and catalytic tetrabutylammonium bromide are added, the mass ratio of hyperbranched poly(ethylene amide) to graphene oxide is 15:3, and stirred to obtain a suspension with a mass fraction of 10 wt%; S2-2. The homogeneous solution obtained in S2-1 is reacted at 150°C for 24h, and then washed and dried to obtain hyperbranched graphene oxide; The preparation method of the hyperbranched barium titanate in S1-2 comprises the following steps: S3-1. The hyperbranched polyamide was added to DMAc and fully dissolved, followed by the addition of barium titanate, the mass ratio of the hyperbranched polyamide to barium titanate being 20:7, and ultrasonic dispersion was performed to obtain a suspension having a mass fraction of 8 wt %; S3-2. The suspension obtained in S3-1 was heated at 55°C and stirred for 20 hours, and then filtered and washed to obtain hyperbranched barium titanate. Example 3 A water-based energy-collecting wear-resistant piezoelectric composite coating for roads, the preparation method of which comprises the following steps: S1. dispersant (sodium salt of polycarboxylate), defoamer (mineral oil) and wetting agent (BYK 346) were added to water in sequence and stirred evenly, and then strip composite electrospun fiber membrane was added, wherein the mass ratio of dispersant, defoamer, wetting agent and strip composite electrospun fiber membrane was 2:0.3:0.3:9, and the suspension A was obtained by stirring; S2. To the suspension A obtained in S1, nano titanium dioxide powder, heavy calcium powder, nano inorganic lead zirconate titanate powder and low-mesh inorganic lead zirconate titanate powder in a mass ratio of 6:10:5:30 are added in sequence and stirred to obtain a suspension B; S3. The suspension B obtained in S2 was mixed with the acrylic emulsion, the mass ratio of the suspension B and the acrylic emulsion was 17:35, and the slurry was obtained after stirring; S4. Methanol is first added to the slurry obtained in S3, and then a defoamer (mineral oil), a thickener (hydroxymethyl cellulose), alcohol ester twelve and water are added in sequence, wherein the mass ratio of methanol, defoamer, thickener, alcohol ester twelve and water is 0.3:0.1:4:5, and a piezoelectric composite coating is obtained after stirring; The method for preparing the strip-shaped composite electrospun fiber membrane in S1 comprises the following steps: S1-1. Take PVDF and PBZ in a mass ratio of 5:8, add them to a DMF / acetone solution in a volume ratio of 6:4, and stir to obtain a homogeneous solution with a mass fraction of 15wt%; S1-2. To the homogeneous solution obtained in S1-1, hyperbranched graphene oxide and hyperbranched barium titanate in a mass ratio of 5:13 were added, and an electrospinning solution with a mass fraction of 10 wt% was obtained after ultrasound; S1-3. The electrospinning solution obtained in S1-2 was spun at a voltage of 15 to 20 kV, a flow rate of 1 mL / h and a receiving distance of 18 cm to obtain an electrospun fiber membrane; S1-4. The electrospun membrane obtained in S1-3 was cut to obtain a membrane with an aspect ratio of 3:1 and an area of 0.2 cm 2 Strip-shaped composite electrospun fiber membrane; Wherein, the preparation method of the hyperbranched graphene oxide in S1-2 comprises the following steps: S2-1. Graphene oxide was dispersed in water and ultrasonically treated, and then hyperbranched poly(ethylene amide) and catalytic tetrabutylammonium bromide were added, the mass ratio of hyperbranched poly(ethylene amide) to graphene oxide was 12:1, and stirred to obtain a suspension with a mass fraction of 8 wt%; S2-2. The suspension obtained in S2-1 was reacted at 120°C for 20h, and then washed and dried to obtain hyperbranched graphene oxide; The preparation method of the hyperbranched barium titanate in S1-2 comprises the following steps: S3-1. The hyperbranched polyamide was added to DMAc and fully dissolved, followed by the addition of barium titanate, the mass ratio of the hyperbranched polyamide to barium titanate being 18:5, and ultrasonic dispersion was performed to obtain a suspension having a mass fraction of 8 wt %; S3-2. The suspension obtained in S3-1 was heated at 40°C and stirred for 20 hours, and then filtered and washed to obtain hyperbranched barium titanate. Example 4 A water-based energy-collecting wear-resistant piezoelectric composite coating for roads, the preparation method of which comprises the following steps: S1. Add dispersant (sodium salt of polycarboxylate), defoamer (mineral oil) and wetting agent (BYK 346) to water in sequence and stir evenly, then add strip composite electrospun fiber membrane, wherein the mass ratio of dispersant, defoamer, wetting agent and strip composite electrospun fiber membrane is 2:0.2:0.2:9, and stir to obtain suspension A; S2. Nano-titanium dioxide powder, heavy calcium powder, nano-inorganic lead zirconate titanate powder and low-mesh inorganic lead zirconate titanate powder were added to the suspension A obtained in S1 in a mass ratio of 7:10:9:30 and stirred to obtain a suspension B; S3. The suspension B obtained in S2 was mixed with the acrylic emulsion, the mass ratio of the suspension B and the acrylic emulsion was 17:25, and a slurry was obtained after stirring; S4. methanol is first added to the slurry obtained in S3, and then a defoamer (mineral oil), a thickener (hydroxymethyl cellulose), alcohol ester twelve and water are added in sequence, wherein the mass ratio of methanol, defoamer, thickener, alcohol ester twelve and water is 0.2:0.08:4:2, and a piezoelectric composite coating is obtained after stirring; The method for preparing the strip-shaped composite electrospun fiber membrane in S1 comprises the following steps: S1-1. Take PVDF and PBZ in a mass ratio of 5:8, add them to a DMF / acetone solution in a volume ratio of 6:4, and stir to obtain a homogeneous solution with a mass fraction of 10wt%; S1-2. To the homogeneous solution obtained in S1-1, hyperbranched graphene oxide and hyperbranched barium titanate in a mass ratio of 5:13 were added, and after ultrasound, an electrospinning solution with a mass fraction of 5 wt% was obtained; S1-3. The electrospinning solution obtained in S1-2 was spun at a voltage of 18 kV, a flow rate of 1 mL / h and a receiving distance of 15 cm to obtain an electrospun fiber membrane; S1-4. The electrospun membrane obtained in S1-3 was cut to obtain a membrane with an aspect ratio of 4:1 and an area of 0.4 cm 2 Strip-shaped composite electrospun fiber membrane; Wherein, the preparation method of the hyperbranched graphene oxide in S1-2 comprises the following steps: S2-1. Graphene oxide is dispersed in water and ultrasonically treated, and then hyperbranched poly(ethylene amide) and catalytic tetrabutylammonium bromide are added, the mass ratio of hyperbranched poly(ethylene amide) to graphene oxide is 12:3, and stirred to obtain a suspension with a mass fraction of 5 wt%; S2-2. The homogeneous solution obtained in S2-1 is reacted at 100°C for 20h, and then washed and dried to obtain hyperbranched graphene oxide; The preparation method of the hyperbranched barium titanate in S1-2 comprises the following steps: S3-1. The hyperbranched polyamide was added to DMAc and fully dissolved, followed by the addition of barium titanate, the mass ratio of the hyperbranched polyamide to barium titanate being 15:1, and ultrasonic dispersion was performed to obtain a suspension having a mass fraction of 4 wt %; S3-2. The suspension obtained in S3-1 was heated at 45°C and stirred for 20 hours, and then filtered and washed to obtain hyperbranched barium titanate. Example 5 A water-based energy-collecting wear-resistant piezoelectric composite coating for roads, the preparation method of which comprises the following steps: S1. Add dispersant (sodium salt of polycarboxylate), defoamer (mineral oil) and wetting agent (BYK 346) to water in sequence and stir evenly, then add strip composite electrospun fiber membrane, wherein the mass ratio of dispersant, defoamer, wetting agent and strip composite electrospun fiber membrane is 3:0.2:0.2:8, and stir to obtain suspension A; S2. To the suspension A obtained in S1, nano titanium dioxide powder, heavy calcium powder, nano inorganic lead zirconate titanate powder and low-mesh inorganic lead zirconate titanate powder in a mass ratio of 7:15:9:35 are added in sequence and stirred thoroughly to obtain a suspension B; S3. The suspension B obtained in S2 was mixed with the acrylic emulsion, the mass ratio of the suspension B and the acrylic emulsion was 18:35, and a slurry was obtained after stirring; S4. methanol is first added to the slurry obtained in S3, and then a defoamer (mineral oil), a thickener (hydroxymethyl cellulose), alcohol ester twelve and water are added in sequence, wherein the mass ratio of methanol, defoamer, thickener, alcohol ester twelve and water is 0.2:0.08:3:5, and a piezoelectric composite coating is obtained after stirring; The method for preparing the strip-shaped composite electrospun fiber membrane in S1 comprises the following steps: S1-1. Take PVDF and PBZ in a mass ratio of 3:5, add them to a DMF / acetone solution in a volume ratio of 6:4, and stir to obtain a homogeneous solution with a mass fraction of 15wt%; S1-2. To the homogeneous solution obtained in S1-1, hyperbranched graphene oxide and hyperbranched barium titanate in a mass ratio of 8:14 were added, and after ultrasound, an electrospinning solution with a mass fraction of PVDF and PBZ of 5 wt% was obtained; S1-3. The electrospinning solution obtained in S1-2 was spun at a voltage of 20 kV, a flow rate of 1.3 mL / h and a receiving distance of 18 cm to obtain an electrospun fiber membrane; S1-4. The electrospun membrane obtained in S1-3 was cut to obtain a membrane with an aspect ratio of 4:1 and an area of 0.4 cm 2 Strip-shaped composite electrospun fiber membrane; Wherein, the preparation method of the hyperbranched graphene oxide in S1-2 comprises the following steps: S2-1. Graphene oxide is dispersed in water and ultrasonically treated, and then hyperbranched poly(ethylene amide) and catalytic tetrabutylammonium bromide are added, the mass ratio of hyperbranched poly(ethylene amide) to graphene oxide is 15:2, and stirred to obtain a suspension with a mass fraction of 8 wt%; S2-2. The homogeneous solution obtained in S2-1 is reacted at 110°C for 20h, and then washed and dried to obtain hyperbranched graphene oxide; The preparation method of the hyperbranched barium titanate in S1-2 comprises the following steps: S3-1. The hyperbranched polyamide was added to DMAc and fully dissolved, followed by the addition of barium titanate, the mass ratio of the hyperbranched polyamide to barium titanate being 15:1, and ultrasonic dispersion was performed to obtain a suspension having a mass fraction of 7wt%; S3-2. The suspension obtained in S3-1 was heated at 40°C and stirred for 20 hours, and then filtered and washed to obtain hyperbranched barium titanate. Example 6 A water-based energy-collecting wear-resistant piezoelectric composite coating for roads, the preparation method of which comprises the following steps: S1. Add dispersant (sodium salt of polycarboxylate), defoamer (mineral oil) and wetting agent (BYK 346) to water in sequence and stir evenly, then add strip composite electrospun fiber membrane, wherein the mass ratio of dispersant, defoamer, wetting agent and strip composite electrospun fiber membrane is 5:0.2:0.3:9, and stir to obtain suspension A; S2. Nano-titanium dioxide powder, heavy calcium powder, nano-inorganic lead zirconate titanate powder and low-mesh inorganic lead zirconate titanate powder were added to the suspension A obtained in S1 in a mass ratio of 9:15:7:30 in sequence and stirred thoroughly to obtain a suspension B; S3. The suspension B obtained in S2 was mixed with the acrylic emulsion, the mass ratio of the suspension B and the acrylic emulsion was 7:30, and a slurry was obtained after stirring; S4. methanol is first added to the slurry obtained in S3, and then a defoamer (mineral oil), a thickener (hydroxymethyl cellulose), alcohol ester twelve and water are added in sequence, wherein the mass ratio of methanol, defoamer, thickener, alcohol ester twelve and water is 0.2:0.09:4:2, and a piezoelectric composite coating is obtained after stirring; The method for preparing the strip-shaped composite electrospun fiber membrane in S1 comprises the following steps: S1-1. Take PVDF and PBZ in a mass ratio of 2:7, add them to a DMF / acetone solution in a volume ratio of 6:4, and stir to obtain a homogeneous solution with a mass fraction of 15wt%; S1-2. To the homogeneous solution obtained in S1-1, hyperbranched graphene oxide and hyperbranched barium titanate in a mass ratio of 5:12 were added, and after ultrasound, an electrospinning solution with a mass fraction of 8 wt% was obtained; S1-3. The electrospinning solution obtained in S1-2 was spun at a voltage of 15 kV, a flow rate of 0.8 mL / h and a receiving distance of 15 cm to obtain an electrospun fiber membrane; S1-4. The electrospun membrane obtained in S1-3 was cut to obtain a membrane with an aspect ratio of 2:1 and an area of 0.3 cm 2 Strip-shaped composite electrospun fiber membrane; Wherein, the preparation method of the hyperbranched graphene oxide in S1-2 comprises the following steps: S2-1. Graphene oxide is dispersed in water and ultrasonically treated, and then hyperbranched poly(ethylene amide) and catalytic tetrabutylammonium bromide are added, the mass ratio of hyperbranched poly(ethylene amide) to graphene oxide is 10:1, and stirred to obtain a suspension with a mass fraction of 3 wt%; S2-2. The homogeneous solution obtained in S2-1 is reacted at 80°C for 18h, and then washed and dried to obtain hyperbranched graphene oxide; The preparation method of the hyperbranched barium titanate in S1-2 comprises the following steps: S3-1. The hyperbranched polyamide was added to DMAc and fully dissolved, followed by the addition of barium titanate, the mass ratio of the hyperbranched polyamide to barium titanate being 15:1, and ultrasonic dispersion was performed to obtain a suspension having a mass fraction of 4 wt %; S3-2. The suspension obtained in S3-1 was heated at 35°C and stirred for 20 hours, and then filtered and washed to obtain hyperbranched barium titanate. Example 7 A water-based energy-collecting wear-resistant piezoelectric composite coating for roads, the preparation method of which comprises the following steps: S1. Add dispersant (sodium salt of polycarboxylate), defoamer (mineral oil) and wetting agent (BYK 346) to water in sequence and stir evenly, then add strip composite electrospun fiber membrane, wherein the mass ratio of dispersant, defoamer, wetting agent and strip composite electrospun fiber membrane is 4:0.3:0.2:10, and stir to obtain suspension A; S2. To the suspension A obtained in S1, nano titanium dioxide powder, heavy calcium powder, nano inorganic lead zirconate titanate powder and low-mesh inorganic lead zirconate titanate powder in a mass ratio of 7:18:9:45 are added in sequence and stirred to obtain a suspension B; S3. The suspension B obtained in S2 was mixed with the acrylic emulsion, the mass ratio of the suspension B and the acrylic emulsion was 13:35, and the slurry was obtained after stirring; S4. methanol is first added to the slurry obtained in S3, and then a defoamer (mineral oil), a thickener (hydroxymethyl cellulose), alcohol ester twelve and water are added in sequence, wherein the mass ratio of methanol, defoamer, thickener, alcohol ester twelve and water is 0.3:0.08:4:2, and a piezoelectric composite coating is obtained after stirring; The method for preparing the strip-shaped composite electrospun fiber membrane in S1 comprises the following steps: S1-1. Take PVDF and PBZ in a mass ratio of 7:5, add them to a DMF / acetone solution in a volume ratio of 6:4, and stir to obtain a homogeneous solution with a mass fraction of 12wt%; S1-2. To the homogeneous solution obtained in S1-1, hyperbranched graphene oxide and hyperbranched barium titanate in a mass ratio of 8:14 were added, and an electrospinning solution with a mass fraction of 10 wt% was obtained after ultrasound; S1-3. The electrospinning solution obtained in S1-2 was spun at a voltage of 20 kV, a flow rate of 1 mL / h and a receiving distance of 18 cm to obtain an electrospun fiber membrane; S1-4. The electrospun membrane obtained in S1-3 was cut to obtain a membrane with an aspect ratio of 5:1 and an area of 0.5 cm 2 Strip-shaped composite electrospun fiber membrane; Wherein, the preparation method of the hyperbranched graphene oxide in S1-2 comprises the following steps: S2-1. Graphene oxide is dispersed in water and ultrasonically treated, and then hyperbranched poly(ethylene amide) and catalytic tetrabutylammonium bromide are added, the mass ratio of hyperbranched poly(ethylene amide) to graphene oxide is 15:2, and stirred to obtain a suspension with a mass fraction of 8 wt%; S2-2. The homogeneous solution obtained in S2-1 is reacted at 130°C for 22h, and then washed and dried to obtain hyperbranched graphene oxide; The preparation method of the hyperbranched barium titanate in S1-2 comprises the following steps: S3-1. The hyperbranched polyamide was added to DMAc and fully dissolved, followed by the addition of barium titanate, the mass ratio of the hyperbranched polyamide to barium titanate being 17:7, and ultrasonic dispersion was performed to obtain a suspension having a mass fraction of 6 wt %; S3-2. The suspension obtained in S3-1 was heated at 45°C and stirred for 20 hours, and then filtered and washed to obtain hyperbranched barium titanate. Comparative Example 1 The difference between this comparative example and Example 7 is that the graphene oxide and barium titanate are not subjected to hyperbranching modification. Comparative Example 2 The difference between this comparative example and Example 7 is that PBZ is not added to the electrospinning solution. Comparative Example 3 The difference between this comparative example and Example 7 is that the hyperbranched graphene oxide and the hyperbranched barium titanate are directly added to the slurry. Comparative Example 4 The difference between this comparative example and Example 7 is that the hyperbranched graphene oxide and the hyperbranched barium titanate are directly added to the slurry without adding the electrospinning fiber membrane. Comparative Example 5 The difference between this comparative example and Example 7 is that no nano inorganic lead zirconate titanate powder is added. Comparative Example 6 The difference between this comparative example and Example 7 is that low-mesh inorganic lead zirconate titanate powder is not added. Performance Testing The wear resistance, pencil hardness, density, piezoelectric coefficient and alkali resistance of the coatings prepared from the coatings prepared in Examples 1-7 of the present invention and Comparative Examples 1-6 were tested below. The results are shown in Table 1. Table 1 Performance test results Note: 1. The wear resistance and alkali resistance test refer to the standard "JT T / 280-2022"; 2. Pencil hardness test refers to the standard "ASTM D3363-2005". Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A water-based energy-collecting wear-resistant piezoelectric composite coating for road use, characterized in that: The preparation method comprises the following steps: S1. Add a dispersant, a defoamer and a wetting agent to water in sequence and stir evenly, then add the strip composite electrospun fiber membrane and stir to obtain a suspension A; S2. Nano-titanium dioxide powder, heavy calcium powder, nano-inorganic lead zirconate titanate powder and low-mesh inorganic lead zirconate titanate powder were sequentially added to the suspension A obtained in S1 and stirred thoroughly to obtain a suspension B; S3. The suspension B obtained in S2 was mixed with an acrylic emulsion and stirred to obtain a slurry; S4. First, methanol is added to the slurry obtained in S3, and then a defoamer, a thickener, alcohol ester twelve and water are added in sequence, and the piezoelectric composite coating is obtained after stirring.
2. The method for preparing the water-based energy-collecting wear-resistant piezoelectric composite coating for road use according to claim 1, characterized in that: The mass ratio of the dispersant, the defoamer, the wetting agent and the strip-shaped composite electrostatic spinning fiber membrane in S1 is 1.5-5: 0.2-0.3: 0.2-0.3: 8-10.
3. The method for preparing the water-based energy-collecting wear-resistant piezoelectric composite coating for road use according to claim 1, characterized in that: The mass ratio of the nano titanium dioxide powder, the heavy calcium powder, the nano inorganic lead zirconate titanate powder and the low-mesh inorganic lead zirconate titanate powder in S2 is 4-10:10-20:5-10:30-50.
4. The method for preparing the water-based energy-harvesting wear-resistant piezoelectric composite coating for road use according to claim 1, characterized in that: The mass ratio of the suspension B to the acrylic emulsion in the S3 is 7-20:25-35, and the solid content of the acrylic emulsion is 55%.
5. The method for preparing the aqueous energy-harvesting wear-resistant piezoelectric composite coating for road use according to claim 1, characterized in that: The mass ratio of the defoamer, thickener, alcohol ester dodecahydrate and water in S4 is 0.2-0.3:0.05-0.1:3-5:2-8.
6. The method for preparing the aqueous energy-harvesting wear-resistant piezoelectric composite coating for road use according to claim 1, characterized in that: The method for preparing the strip-shaped composite electrospun fiber membrane in S1 comprises the following steps: S1-1. Take PVDF and PBZ in a mass ratio of 2 to 7:3 to 8, add them to a DMF / acetone solution in a volume ratio of 6:4, and stir to obtain a homogeneous solution with a mass fraction of 10 to 25 wt%; S1-2. To the homogeneous solution obtained in S1-1, hyperbranched graphene oxide and hyperbranched barium titanate in a mass ratio of 1 to 8:1 to 15 are added, and after ultrasonication, an electrospinning solution with a mass fraction of 5 to 15 wt% is obtained; S1-3. The electrospinning solution obtained in S1-2 was spun at a voltage of 15 to 20 kV, a flow rate of 0.8 to 1.5 mL / h and a receiving distance of 15 to 20 cm to obtain an electrospun fiber membrane; S1-4. The electrospun membrane obtained in S1-3 was cut to obtain an aspect ratio of 2 to 5:1 and an area of 0.1 to 0.5 cm 2 Strip-shaped composite electrospun fiber membrane.
7. The method for preparing the aqueous energy-harvesting wear-resistant piezoelectric composite coating for road use according to claim 6, characterized in that: The preparation method of the hyperbranched graphene oxide in S1-2 comprises the following steps: S2-1. The graphene oxide was dispersed in water and ultrasonically treated, followed by adding hyperbranched poly(ethylene amide) and catalytic tetrabutylammonium bromide and stirring to obtain a suspension; S2-2. The suspension obtained in S2-1 is reacted at 80-150° C. for 18-24 h, and then washed and dried to obtain hyperbranched graphene oxide.
8. The method for preparing the aqueous energy-harvesting wear-resistant piezoelectric composite coating for road use according to claim 6, characterized in that: The preparation method of the hyperbranched barium titanate in S1-2 comprises the following steps: S3-1. Add hyperbranched polyamide into DMAc and fully dissolve it, then add barium titanate and ultrasonically disperse it to obtain a suspension; S3-2. Heat the suspension obtained in S3-1 at 35-55°C with stirring for 20 hours, then filter and wash to obtain hyperbranched barium titanate.
9. The method for preparing the aqueous energy-harvesting wear-resistant piezoelectric composite coating for road use according to claim 7, characterized in that: The mass ratio of hyperbranched polyvinyl amide to graphene oxide in S2-1 is 10-15:1-3, and the mass fraction of the suspension is 3-10wt%.
10. The method for preparing the aqueous energy-harvesting wear-resistant piezoelectric composite coating for road use according to claim 8, characterized in that: The mass ratio of the hyperbranched polyamide to the barium titanate in the S3-1 is 15-20:1-7, and the mass fraction of the suspension is 4-8wt%.
Citation Information
Patent Citations
Method for preparing composite piezoelectric material based on electrostatic spinning process
CN115045044A
PPO-based dielectric composite material and preparation method thereof
CN115850946A
Thermosetting piezoelectric composites and their use in additive manufacturing
CN117120547A
Preparation method and catalytic sterilization application of DA-Ag-BCZT / PVDF flexible piezoelectric composite fiber film
CN118407192A
Barium titanate fiber, resin composition containing same, polymer composite piezoelectric body, piezoelectric element, method for producing barium titanate fiber, and method for producing polymer composite piezoelectric body
US20220416152A1